Finer Distinctions: Variability in Satisfied Older Couples' Problem‐Solving Behaviors. Issue 2 (4th November 2015) - Rauer, Amy; Williams, Leah; Jensen, Jakob
Abstract : This study utilized observational and self‐report data from 64 maritally satisfied and stable older couples to explore if there were meaningful differences in how couples approached marital disagreements. Using a typology approach to classify couples based on their behaviors in a 15‐minute problem‐solving interaction, findings revealed four types of couples: (1) problem solvers (characterized by both spouses' higher problem‐solving skills and warmth), (2) supporters (characterized by both spouses' notable warmth), (3) even couples (characterized by both spouses' moderate problem‐solving skills and warmth), and (4) cool couples (characterized by both spouses' greater negativity and lower problem‐solving skills and warmth). Despite the differences in these behaviors, all couples had relatively high marital satisfaction and functioning. However, across nearly all indices, spouses in the cool couple cluster reported poorer marital functioning, particularly when compared to the problem solvers and supporters. These findings suggest that even modest doses of negativity (e.g., eye roll) may be problematic for some satisfied couples later in life. The implications of these typologies are discussed as they pertain to practitioners' efforts to tailor their approaches to a wider swath of the population.